Flavylium Salts: A Blooming Core for Bioinspired Ionic Liquid Crystals. Issue 56 (18th September 2019) - Forschner, Robert; Knelles, Jakob; Bader, Korinna; Müller, Carsten; Frey, Wolfgang; Köhn, Andreas; Molard, Yann; Giesselmann, Frank; Laschat, Sabine
Abstract: Thermotropic ionic liquid crystals based on the flavylium scaffold have been synthesized and studied for their structure‐properties relationship for the first time. The mesogens were probed by differential scanning calorimetry (DSC), polarizing optical microscopy (POM), and X‐ray diffraction (XRD). Low numbers of alkoxy side chains resulted in smectic (SmA) and lamello‐columnar (LamCol ) phases, whereas higher substituted flavylium salts showed Colro as well as ordered and disordered columnar (Colho, Colhd ) mesophases. Mesophase width ranged from 13 K to 220 K, giving access to room temperature liquid crystals. The optical properties of the synthesized compounds were probed towards absorption and emission properties. Strong absorption with maxima between 444 and 507 nm was observed, and some chromophores were highly emissive with quantum yields up to 99 %. Ultimately, mesogenic and dye properties were examined by temperature‐dependent emissive experiments in the solid state. Abstract : Flower power : In the search for new mesogenic cores for ionic liquid crystals, the authors were inspired by anthocyanidins, which are responsible for the bright red to blue colors in many plants. The new flavylium triflates were examined for their liquid crystalline and dye properties.